Breaking through the Justice Wall for the Underprivileged People In Criminal Cases - Nurtresna, Robby; Mabsuti, Mabsuti; Hidayat, Syahril; Putri, Nabila (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
The motto “Justitiae Non Est Neganda, Non Differenda” ("Justice must not be denied and must not be delayed") should guide law enforcement in Indonesia. However, in reality, individuals from lower-middle or underprivileged socioeconomic backgrounds who are involved in criminal cases often encounter significant barriers to obtaining substantial justice. This study aims to assess the availability of access to justice for these vulnerable groups and to develop practical solutions to ensure equitable legal protection. Using empirical legal research supported by primary and secondary data, combined with legislative and case law approaches, the study employs descriptive and analytical techniques. The findings reveal that although the legal system guarantees equality before the law, structural, economic, and institutional constraints continue to hinder fair treatment. The novelty of this study lies in proposing a practical mechanism for resolving criminal cases that prioritizes the disadvantaged, thereby bridging the gap between legal norms and social realities. A strong commitment from law enforcement, along with implementable reforms, is essential to make justice accessible to all.